Drug resistance in B and non-B subtypes amongst subjects recently diagnosed as primary/recent or chronic HIV-infected over the period 2013–2016: Impact on susceptibility to first-line strategies including integrase strand-transfer inhibitors. (September 2017) - Andreis, Samantha; Basso, Monica; Scaggiante, Renzo; Cruciani, Mario; Ferretto, Roberto; Manfrin, Vinicio; Panese, Sandro; Rossi, Maria Cristina; Francavilla, Ermenegildo; Boldrin, Caterina; Alvarez, Mario; Dal Bello, Federico; et al.
Highlights: Major InSTI-TDRM is rarely found in HIV patients diagnosed in 2013–2016. NNRTI-related mutation persisted, sometimes impacting on modern NNRTI drugs. All new HIV diagnosed patients should be tested for TDRMs including integrase region. Non-B subtypes are different in Italian and foreign subjects. Abstract: Objectives: To characterize the prevalence of transmitted drug resistance mutations (TDRMs) by plasma analysis of 750 patients at the time of HIV diagnosis from January 1, 2013 to November 16, 2016 in the Veneto region (Italy), where all drugs included in the recommended first line therapies were prescribed, included integrase strand transfer inhibitors (InNSTI). Methods: TDRMs were defined according to the Stanford HIV database algorithm. Results: Subtype B was the most prevalent HIV clade (67.3%). A total of 92 patients (12.3%) were expected to be resistant to one drug at least, most with a single class mutation (60/68–88.2% in subtype B infected subjectsand 23/24–95.8% in non-B subjects) and affecting mainly NNRTIs. No significant differences were observed between the prevalence rates of TDRMs involving one or more drugs, except for the presence of E138A quite only in patients with B subtype and other NNRTI in subjects with non-B infection. The diagnosis of primary/recent infection was made in 73 patients (9.7%): they had almost only TDRMs involving a single class. Resistance to InSTI was studied in 484 subjects (53 with primary-recent infection), one patient had 143C in 2016, a total of thirteen 157Q mutations were detected (only one in primary/recent infection). Conclusions: Only one major InSTI-TDRM was identified but monitoring of TDRMs should continue in the light of continuing presence of NNRTI-related mutation amongst newly diagnosed subjects, sometime impacting also to modern NNRTI drugs recommended in first-line therapy.